O patrimônio cultural nas cidades inteligentes - Juliana Martins de Castro Barroso (2020)
The study “Cultural heritage in smart cities” aims to investigate the heritage preservation in the current discussions on smart cities, a perspective of government oriented to issues such as sustainability, livability, citizen participation and the use of technologies. Therefore, bibliographic and documentary sources were analyzed about smart heritage preservation area and smart initiatives carried out in three different Brazilian cities: Sao Paulo, Rio de Janeiro and Belo Horizonte. This research aimed to define and characterize the field of “smart” heritage, being closely linked to smart city projects and the use of new technologies to improve the heritage preservation and diffusion; as well as investigate the approach taken to cultural and heritage issues in national smart projects of the last decade. This is an exploratory qualitative research that made use of the methodological procedures of systematic literature review to characterize the field of smart heritage and case study to understand the national reality. The Brazilian cities that were part of the case study were chosen based on their presence and position in international and national smart city rankings, and the data about them were collected between documentation and news provided by the municipalities, being coded by content analysis. As results, it is pointed out that, although the existence of important initiatives for the cultural and heritage field in the smart projects recovered internationally, in the Brazilian context these areas have not yet been involved in discussions and actions related to smart cities.